Reflections on the flow of emotion in environmental research - Tajuddin, Nor Azlin (World Anthropologies Network, 2010)
In this article I provide a reflexive account of my emotions both prior to and during fieldwork. I begin with a personal narrative that explores my motivations for conducting a study on a pertinent environmental issue – river pollution. My comparative ethnographic fieldwork in two different socio-cultural and environmental settings, that of the Klang River in Kuala Lumpur and the Torrens River in Adelaide, yielded stories, pictures, and/or a spectrum of emotions about people’s interactions with the rivers, some of which resonated with my own. On the one hand, positive emotions during fieldwork were triggered, for example, when I observed colourful flora and fauna in certain section of the rivers. On the other hand, I experienced negative feelings when I observed floating rubbish and trash racks installed across the rivers. I describe these personal fieldwork experiences, alongside a discussion about my own reflections. Finally, and in light of my fieldwork experience, I briefly suggest implications for ethnographic research and methodological practice.